Identification of Electrical Properties of Bio-battery based on Spent Coffee Grounds - Pawarangan, Ishak; Jefriyanto, Wilson (BULETIN FISIKA, 2021)
Principally, renewable energy technology produces energy by converting natural resources into useful forms of energy. Bio-battery is an alternative natural energy source that utilizes nanoparticles from plants to generate electricity. In this study, coffee grounds were used as an electrolyte paste to produce bio-battery. This study aims to determine the potential use of spent coffee grounds as an electrolyte paste. Furthermore, the analysis of the composition of the best coffee grounds to produce the optimum current and the level of effectiveness of the bio-battery in terms of the current value. To determine whether there is an effect of coffee grounds concentration on the resulting current, a series of experiments were carried out to determine the best composition between the type and concentration of coffee grounds. Characterization of the device produces a maximum voltage of 1.11 ± 0.09 V and a power of 0.25 mW. The combination of series and parallel needs to be developed to achieve higher circuit voltages and power.